2023
DOI: 10.1186/s12941-023-00553-7
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal colonization with group B Streptococcus and antibiotic resistance in China: systematic review and meta-analyses

Abstract: Background Maternal rectovaginal colonization with group B Streptococcus (GBS) or Streptococcus agalactiae is the most common pathway for this disease during the perinatal period. This meta-analysis aimed to summarize existing data regarding maternal colonization, serotype profiles, and antibiotic resistance in China. Methods Systematic literature reviews were conducted after searching 6 databases. Meta-analysis was applied to analyze colonization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This measure effectively reduces the incidence of GBS in newborns. Penicillin is recommended as the rst-choice drug for IAP in various countries [6][7].The global detection rate of GBS in pregnant women varies by region, and reports show that the colonization rate of GBS in pregnant women worldwide is approximately 17.4% (95% CI 16.3% -18.5%) [5].The overall colonization rate of GBS among pregnant women in China is 8.1% (95% CI, 7.2-8.9) [2], with the highest rate being 9.3% (95% CI 6.6-12.0) in the central region, followed by 8.3% (95% CI 5.5-11.0) in the eastern region, and the lowest rate being 6.8% (95% CI 5.4-8.3) in the western region [8].The GBS colonization rate of pregnant women in this study was 6.52%, which is lower than the domestic and global average. The differences in colonization rates among different studies or regions may be related to regional differences, detection methods (culture/PCR), sampling sites (vaginal/rectal sampling), and differences in sampling gestational weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This measure effectively reduces the incidence of GBS in newborns. Penicillin is recommended as the rst-choice drug for IAP in various countries [6][7].The global detection rate of GBS in pregnant women varies by region, and reports show that the colonization rate of GBS in pregnant women worldwide is approximately 17.4% (95% CI 16.3% -18.5%) [5].The overall colonization rate of GBS among pregnant women in China is 8.1% (95% CI, 7.2-8.9) [2], with the highest rate being 9.3% (95% CI 6.6-12.0) in the central region, followed by 8.3% (95% CI 5.5-11.0) in the eastern region, and the lowest rate being 6.8% (95% CI 5.4-8.3) in the western region [8].The GBS colonization rate of pregnant women in this study was 6.52%, which is lower than the domestic and global average. The differences in colonization rates among different studies or regions may be related to regional differences, detection methods (culture/PCR), sampling sites (vaginal/rectal sampling), and differences in sampling gestational weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It is a conditional pathogen, mainly colonized in the lower digestive tract and urogenital tract of the human body. Occasional carriers in the normal population do not cause obvious symptoms, and physiological changes during pregnancy can affect the reproductive tract microenvironment, increasing the risk of GBS infection [1].GBS is listed as one of the main pathogenic bacteria for perinatal maternal and infant infections, and it is reported that the colonization rate of GBS in pregnant women in China is about 8.1% [2].GBS infection can increase the risk of late pregnancy abortion, premature rupture of membranes, Postpartum bleeding, puerperal infection, and other diseases, and also easily induce Neonatal infection, Neonatal jaundice and other diseases [3].The American College of Obstetricians and Gynecologists (ACOG) recommends GBS screening for all pregnant women aged 35-37 weeks, and intrauterine antibiotic prophylaxis (IAP) for pregnant women with GBS colonization or risk factors [4]. This measure signi cantly reduces the incidence of early onset GBS sepsis by 50% -80% [5], and penicillin is the preferred drug for IAP.…”
Section: Introductionmentioning
confidence: 99%
“…Additional study is needed to elucidate the phenotypic resistance profiles of ST283 and correlation with antimicrobial resistance genes. GBS phenotypic resistance to macrolides and fluoroquinolones vary regionally but remain concerning given the burden of invasive GBS infection globally [ 29 ]. Although the prevalence of multi-drug resistance gene carriage in ST283 is currently low, increasing use of medically important antimicrobials in the freshwater aquaculture industry [ 30 ] and in humans—particularly in low- and middle-income countries [ 31 ]—risks the generation of expanded resistance profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Before 2020 it was between 11.5-14.3% for Japanese GAS isolates [86] and 11% for Iranian GBS isolates [47]. However, reports from China indicate that there has been a dramatic increase in quinolone-resistant GBS isolates in pregnant women, with rates increasing up to 72.9% in 2021 [95]. In Africa, the evolution of this resistance varied between 7.2% for Ethiopian GAS [51] to 24.56% for GBS in this region [69].…”
Section: Resistance To Fluoroquinolonesmentioning
confidence: 99%